STUDENTS’ PROPORTIONAL REASONING IN MATHEMATICS THROUGH COVID-19 PANDEMIC CONTEXT - Rohati, Rohati; Turmudi, Turmudi; Kusnandi, Kusnandi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
Abstract The aim of this study was to ascertain high school students' proportional reasoning in the sense of the COVID-19 pandemic. How do students' thoughts flow when confronted with problems requiring proportional reasoning? This research is a mixed study by collecting data through problem-solving questions to 253 junior high school students in Muaro Jambi, Jambi Province, Indonesia. The problem-solving activities are based on real-world scenarios and require reasoning that is proportional and pertinent to the COVID-19 pandemic context. Due to the ongoing COVID-19 pandemic, the test is administered through the Whatsapp framework. Students' responses are examined in detail to ascertain their proportional reasoning skills. The results indicate that almost all students correctly answered the first question. However, only a small percentage of students were able to answer to and make the correct argument for the second question. The findings indicated that students demonstrated a reasonable level of proportional reasoning when confronted with the COVID-19 pandemic situation. According to the findings of this report, it is important for teachers of mathematics to establish learning activities and problem-solving tasks that help students improve their proportional reasoning skills. Keywords: COVID-19; Problem Solving; Proportional Reasoning; Real-World Situations AbstrakTujuan dari penelitian ini adalah untuk menggali penalaran proporsional siswa SMA  dengan konteks pandemi COVID-19. Bagaimana alur pemikiran siswa ketika dihadapkan pada masalah yang membutuhkan penalaran proporsional? Penelitian ini merupakan penelitian campuran dengan pengumpulan data melalui pertanyaan pemecahan masalah kepada 253 siswa SMP di Muaro Jambi, Provinsi Jambi, Indonesia. Kegiatan pemecahan masalah didasarkan pada skenario dunia nyata dan membutuhkan penalaran yang proporsional dan relevan dengan konteks pandemi COVID-19. Karena pandemi COVID-19 yang sedang berlangsung, tes dikirim melalui aplikasi Whatsapp. Tanggapan siswa diperiksa secara rinci untuk memastikan kemampuan penalaran proporsional mereka. Hasilnya menunjukkan bahwa hampir semua siswa menjawab pertanyaan pertama dengan benar. Namun, hanya sebagian kecil siswa yang mampu menjawab dan membuat argumen yang benar untuk pertanyaan kedua. Hasil penelitian menunjukkan bahwa siswa memiliki alur penalaran proporsional yang cukup baik dengan menggunakan konteks kondisi pandemi COVID-19. Menurut temuan  ini, penting bagi guru matematika untuk menetapkan kegiatan pembelajaran dan tugas pemecahan masalah yang membantu siswa meningkatkan keterampilan penalaran proporsional mereka. Kata kunci: COVID-19; Pemecahan Masalah; Penalaran Proporsional; Situasi Dunia